Spatial–temporal analysis of pulmonary tuberculosis among students in the Zhejiang Province of China from 2007–2020 - Zhang, Mengdie; Chen, Songhua; Luo, Dan; Chen, Bin; Zhang, Yu; Wang, Wei; Wu, Qian; Liu, Kui; Wang, Hongmei; Jiang, Jianmin (Frontiers in Public Health, 2023)
Background: Pulmonary tuberculosis (PTB) is a serious chronic communicable disease that causes a significant disease burden in China; however, few studies have described its spatial epidemiological features in students. Methods: Data of all notified PTB cases from 2007 to 2020 in the student population were collected in the Zhejiang Province, China using the available TB Management Information System. Analyses including time trend, spatial autocorrelation, and spatial–temporal analysis were performed to identify temporal trends, hotspots, and clustering, respectively. Results: A total of 17,500 PTB cases were identified among students in the Zhejiang Province during the study period, accounting for 3.75% of all notified PTB cases. The health-seeking delay rate was 45.32%. Joinpoint regression analysis for notified PTB incidence revealed a decreased trend while spatial analysis showed the clustering with high risk in the western area of Zhejiang Province. Additionally, one most likely cluster along with three secondary clusters was identified by spatial–temporal analysis. Conclusion: The notified incidence of PTB cases among students showed a downward trend while that of the bacteriologically confirmed cases presented an increase trend since 2017. The risk of PTB among senior high school and above was higher than that of junior high school students. Besides, the western area of Zhejiang Province was the high-risk area of student PTB and more comprehensive interventions should be performed such as admission screening and routine health monitoring to improve PTB early identification.